Resistensi Kritis Ki Hadjar Dewantara pada Surat Kabar De Express: Sebuah Kajian Postkolonialisme - Masjid, Akbar Al; Trisharsiwi, Trisharsiwi; Setiawan, Arya Dani; Marwanti, Endah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Postcolonialism literary criticism is a critical approach to literature that involves the historical context of colonialism and its impact on culture, identity, and power. Postcolonial literary criticism also helps provide an understanding of the concept of 'the Other', i.e., the way in which colonial culture denigrates and belittles other cultures outside its nation. This study aims to examine the article by Ki Hadjar Dewantara written in the newspaper Express with an approach to literary criticism of postcolonialism. This type of research is a descriptive qualitative literature study with an analysis method, namely content analysis. The source of this research data is an article entitled